2004
DOI: 10.1103/physrevb.70.014105
|View full text |Cite
|
Sign up to set email alerts
|

Absence of metastable states in strained monatomic cubic crystals

Abstract: A tetragonal, or Bain path, distortion of a metal with an fcc (bcc) ground state toward the bcc (fcc) structure initially requires an increase in energy, but at some point along the Bain path the energy will again decrease until a local minimum is reached. Using a combination of parametrized tight-binding and first-principles linearized augmented plane wave calculations, we show that this local minimum is unstable with respect to an elastic distortion, except in the rare case that the minimum is at the bcc (fc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…A negative c 66 corresponds to an unstable long-wavelength part of the transverse phonon mode T [100] [0ξ0]. Apart from Ta, this elastic instability was reported before [24,60]. To complete the picture of the bcc transition metals, we note that Fe was predicted to order antiferromagnetically and to be unstable due to c 66 < 0 at the bct local minimum of its EBP [61].…”
Section: B Elements With Stable Cubic Structurementioning
confidence: 92%
“…A negative c 66 corresponds to an unstable long-wavelength part of the transverse phonon mode T [100] [0ξ0]. Apart from Ta, this elastic instability was reported before [24,60]. To complete the picture of the bcc transition metals, we note that Fe was predicted to order antiferromagnetically and to be unstable due to c 66 < 0 at the bct local minimum of its EBP [61].…”
Section: B Elements With Stable Cubic Structurementioning
confidence: 92%
“…Mehl et al (2004) investigated this extended tetragonal Bain path in some detail for elements that are thermodynamically stable in fcc or bcc structures. For Sr the secondary minimum coincides with the bcc lattice, and for Ba with the fcc lattice.…”
Section: Effect Of Anharmonicitymentioning
confidence: 99%
“…In all the cases, we find imaginary phonon frequencies that clearly indicate the dynamic instability of bulk Ru and Os, in the bct structure. It should be noted that the imaginary phonon branch in the Γ → X direction reveals an elastic instability related to a negative value of the elastic constant C ′ = (c 11 − c 12 )/2 [1,7,18]. Additionally, the effect of the epitaxial and uniaxial strains on the phonon dispersion was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the prediction of a ferromagnetic order in the local minimum of the Bain path for Ru and Os in the bct structure with c/a < 1, a study on the dynamical stability in these materials has not yet been reported to the best of our knowledge. From a theoretical point of view, the stability analysis of a given crystal structure is necessary to evaluate if under small deformations of the lattice, the atoms return to their assumed equilibrium position, which identify a truly metastable phase [1,7,8,9].…”
Section: Introductionmentioning
confidence: 99%